The Influence Of Some Financial Ratios, Sales Growth And Debt Maturity On Financial Performance - ARISUDHANA, Dicky (Journal of Governance, Taxation and Auditing, 2023)
This research aims to determine and test the influence of several financial ratios, namely liquidity, leverage, sales growth and debt maturity on financial performance. This type of research is quantitative research which uses secondary data sourced from the website www.idx.co.id. The population in this study are food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange with an observation period of 2018-2022. The sampling technique used a purposive sampling method and a total sample of 44 companies was obtained. The analytical method in this research uses multiple linear regression tests with data processing using SPSS version 22 software. The results of the research show that liquidity as proxied by the current ratio and sales growth has a significant effect in a positive direction on financial performance, while leverage and debt maturity have a significant effect in a negative direction. on financial performance.